Vibration and Dynamic Response of Buffering Devices during the Vertical Feeding of Coal Mine Solid Backfill Materials - Feng Ju; Zequan He; Meng Xiao; Peng Huang; Shuai Guo (Advances in Civil Engineering)
The stability of buffering devices is very important for the continuous vertical feeding of solid backfill materials. Based on the characteristics of the vertical feeding system, the functional characteristics of buffering devices were analyzed and a buffering device was designed in this paper. The finite element models for the buffering device were established by using the ANSYS software, and the dynamic response and mode characteristics of these models were studied. The results show that the distribution of the equivalent stress on the buffering device surface is petal shaped, in which the stress reaches the maximum at the center and gradually decrease to all around. The stress of support beams is highest at both ends and lowest at the center. Besides, the resonant frequency of this buffering device is 2.4 Hz, which means this frequency should be avoided during the process of backfill materials feeding. This buffering device was used in Wugou Coal Mine, and the monitoring result shows that the maximum displacement of the buffering device is about 65 mm, which means this device is in a good operating condition.